5(3t-4)-6=12t+4

Simple and best practice solution for 5(3t-4)-6=12t+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3t-4)-6=12t+4 equation:


Simplifying
5(3t + -4) + -6 = 12t + 4

Reorder the terms:
5(-4 + 3t) + -6 = 12t + 4
(-4 * 5 + 3t * 5) + -6 = 12t + 4
(-20 + 15t) + -6 = 12t + 4

Reorder the terms:
-20 + -6 + 15t = 12t + 4

Combine like terms: -20 + -6 = -26
-26 + 15t = 12t + 4

Reorder the terms:
-26 + 15t = 4 + 12t

Solving
-26 + 15t = 4 + 12t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-12t' to each side of the equation.
-26 + 15t + -12t = 4 + 12t + -12t

Combine like terms: 15t + -12t = 3t
-26 + 3t = 4 + 12t + -12t

Combine like terms: 12t + -12t = 0
-26 + 3t = 4 + 0
-26 + 3t = 4

Add '26' to each side of the equation.
-26 + 26 + 3t = 4 + 26

Combine like terms: -26 + 26 = 0
0 + 3t = 4 + 26
3t = 4 + 26

Combine like terms: 4 + 26 = 30
3t = 30

Divide each side by '3'.
t = 10

Simplifying
t = 10

See similar equations:

| -3r+6=r-6 | | 10-3y=6 | | 8u=7u+1 | | 18-13=1/2a=3/4a-5/8a | | 2z/7-2=7 | | 8y+4-6y=8+y+1 | | -8y-20=5y-20 | | -10q=-9q+6 | | Y=9+-0.5x | | 1/3(6n-9) | | -2(x-3)=x+24 | | 7xblank=84 | | 2(3y+5)=5(y+1) | | 36=I^2*9 | | 6x+-2(x+4)=12 | | 9-1(-1-3y)=4+y-(3-y) | | -2x-6=x+24 | | 4y+3y=2 | | 27=-9/11y | | log(x+6)= | | 5x-6=8x+3 | | Y=x(x-8) | | 4a-9whena=7 | | 143=c | | 2+y=-28 | | Z/7-9=4 | | -3/5x=17/15 | | -6x+2(x+4)=12 | | 16=4w+2-2 | | -10-5v=-10v | | .5x+0.1=0.6-(-5) | | -10-5v=10v |

Equations solver categories